A compact single layer dual band microstrip patch antenna for 5G terminal applications - Xin-Hao Ding; Zhen Tan; Shah Nawaz Burokur (Scientific Reports)
Abstract In modern applications, the shrinking available space on terminals coupled with the increasing number of frequency bands has prompted the greatest demand for antenna miniaturization and multi-band features. This work introduces an innovative method for designing a dual-band planar antenna with an exceptionally compact size, addressing the pressing requirement. Two half-mode patches, both operating in two modes (TM0.5,0 of 3.5 GHz frequency band and TM0.5,2 of 4.9 GHz frequency band) are placed back-to-back. The dual-mode operation in the 3.5 GHz band is achieved using the two TM0.5,0 modes and the dual-mode operation in the 4.9 GHz band is obtained from the TM0.5,2 and strip modes. Then, based on the elementary antenna design, a 4 × 4 MIMO system is designed and measured. The isolation between the elements is found to be greater than 15.5 dB. The proposed antenna achieves a bandwidth coverage of 3.36–3.70 GHz and 4.79–5.01 GHz, corresponding to N78 and N79 frequency bands of the fifth generation (5G) wireless communication systems, respectively. The proposed antenna, based on a single-layer design without any air spacing, features a compact size and high integration density, making it an interesting solution for 5G terminals.